1999
DOI: 10.1111/j.1574-695x.1999.tb01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular methods for typing ofHelicobacter pyloriand their applications

Abstract: Microbial typing is a useful tool in clinical epidemiology for defining the source and route of infection, for studying the persistence and reinfection rates, clonal selection in the host and bacterial evolution. Phenotypic methods such as biotyping, serotyping and hemagglutinin typing have little discriminatory power compared to genotypic methods concerning the typing of Helicobacter pylori. Therefore great efforts have been made to establish useful molecular typing methods. In this context, the most frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…One of the main proteins of H. pylori is urease and the genes encoding this and their accessory proteins have been studied for PCR because these genes are highly conserved in H. pylori [15][16][17]. Analysis of smaller fragments of the urease C and urease B genes using the restriction enzymes HaeIII and MboI demonstrated that the genomic structure of H. pylori was highly diverse [18].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main proteins of H. pylori is urease and the genes encoding this and their accessory proteins have been studied for PCR because these genes are highly conserved in H. pylori [15][16][17]. Analysis of smaller fragments of the urease C and urease B genes using the restriction enzymes HaeIII and MboI demonstrated that the genomic structure of H. pylori was highly diverse [18].…”
Section: Introductionmentioning
confidence: 99%